Brain magnetic resonance imaging helps to differentiate atypical multiple sclerosis with cavitary lesions and vanishing white matter disease. (4th January 2016) - Ayrignac, X.; Menjot de Champfleur, N.; Menjot de Champfleur, S.; Carra‐Dallière, C.; Deverdun, J.; Corlobe, A.; Labauge, P.
Abstract : Background and purpose: Multiple sclerosis (MS) patients can present with atypical cavitary lesions mimicking vanishing white matter disease (VWMD). Our objective was to identify brain magnetic resonance imaging (MRI) findings that differentiate these two disorders. Methods: A cross‐sectional study was performed including 14 patients with MS with cavitary lesions and 14 patients with VWMD. Two neuroradiologists retrospectively reviewed the MRI including at least T1‐, T2‐ and fluid‐attenuated inversion recovery weighted images. Results: The main differences included ovoid lesions perpendicular to the lateral ventricle, punctate isolated juxtacortical lesions (both 100% in MS versus 0% in VWMD) and symmetrical infratentorial hyperintensities (0% in MS versus 50% in VWMD). Other statistically significant differences included midbrain (79% in MS versus 29% in VWMD) and thalamus lesions (71% vs. 7%) as well as extensive external capsule involvement (29% vs. 86%) and extensive corpus callosum lesions (64% vs. 100%). Cavitary lesions usually had periventricular predominance in MS (36% vs. 0%) whereas they were more frequently anterior in VWMD (0% in MS versus 57% in VWMD). Conclusion: Despite many similar MRI findings, our results suggest that a careful analysis of the morphology and the location of the lesions is helpful to differentiate these distinct disorders. Abstract : Clickhere for the corresponding questions to this CME article.